Determinants of Ethical Behavior of Accounting Students - Sampewai, Helmaise; Amir, Andi Mattulada; Jurana, Jurana; Abdullah, Muhammad Ikbal; Din, Muhammad; Ternripada, Ternripada (Terbuka Journal of Economics and Business, 2022)
The research aims to test and analyze the influence of business and professional ethics education, love of money, and religiosity on the ethical behavior of accounting students. The research method used is quantitative research. Respondents in this study were undergraduate students of the Department of Accounting, Faculty of Economics and Business, Tadulako University with a sample of 90 people consisting of the class of 2016, 2017, and 2018. Data collection technique by distributing questionnaires through google form. Data analysis techniques use multiple linear regression analysis with the help of SPSS analysis tool version 22 for windows. The results showed that the educational variables of business ethics and professions had a positive effect on the ethical behavior of accounting students, as well as the variables of love of money and religiosity positively on the ethical behavior of accounting student